Energy distributions of copper ions and atoms sputtered by atomic and molecular ions - Wang, L.; Nor, R.M.; Graham, W.G. (Institute of Physics, 1997)
Non-resonant multiphoton ionization combined with quadrupole and time-of-flight analysis has been used to study sputtering by both atomic and molecular ion beams. The mass spectra and energy distributions of both sputtered atoms and secondary ions produced by 3.6 keV Ar+, N+, N-2(+), CF2+ and CF3+ ion bombardment at 45 degrees to a polycrystalline copper target have been measured. The energy distributions of the copper ions and atoms are found to be different and quite complex. The ion distributions can generally be described by a linear collision cascade model, with possible evidence for a knock-on contribution. The sputtered atom distributions are partially described by a combination of linear collision cascade and dense cascade (thermal spike) models. This is interpreted as support for a time-evolving sputtering mechanism.